On QoS-Aware Publish-Subscribe - Position Paper - Araújo, Filipe (2009)
This position paper addresses the issue of supporting quality-of-service (QoS) parameters in distributed publish-subscribe systems. It advocates that QoS parameters should be handled using the same constructs as other information regarding events, such as their type or content. At the same time, we claim that the use of a consistent set of mechanisms should not preclude to decouple the specification of QoS properties from the specification of type, subject or content-based constraints. We also advocate that QoS parameters should not be embedded on the type or content of the events. We show that some QoS parameters can only be computed in run-time, as they depend on dynamic aspects such as the location of the participants and the system load. The paper proposes a model that supports the decoupling of QoS characterization from the event characterization while, at the same time, offers an uniform treatment of both aspects